MULTI-YEAR SPORTS TRAINING IS A LONG-TERM PEDAGOGICAL PROCESS CHARACTERIZED BY A SPECIFIC PROGRAM FOR CERTAIN AGE GROUPS - Akmalovich, Dustov Bakhtiyor (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
In this article, the preparation of children for the first competition is carried out by a physical education teacher in a school setting, students can be selected on the basis of the program and with the help of assessment exercises, active folk games. These qualifiers are widely covered in order to be very close to the essence of the game of volleyball